Developing High Order Thinking Skill in the Context of Mathematical Learning in Primary School - Fajri, Muhammad (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this paper is to describe about high order thinking skill in matematic learning in primary school. High order thinking skills are absolutely necessary for students to equip them in the context of 21st learning century. In the primary school, the implementation is embedded in the curriculum framework currently used to develop high order thinking skills in the learning process. In addition, the competency of learning is also affiliated with the achievement of 21st learning century skills. The process of learning mathematics, is not purely only learn how to count in the implementation of learning that done. This is in line with the high level of expected competence related to the development of high order thinking skills by referring to the development of 21st learning century contexts in the primary school classes. This developed of high order thinking skills refers to Bloomâs taxonomy that has been revised by Anderson, et.al. Based on these taxonomy, the high order thinking skills is consists of from 3 levels of the 6 levels developed at levels 4 through 6. These three levels among others, are: (1) analyze; (2) evaluation; (3) create. These three levels in the cognitive domain are implemented through a series of mathematics learning processes in primary school. In the process, the development of cognitive abilities at such a high level can be implemented by provising high order thinking skills challenges to enable meaningful learning in the mathematics learning process in primary schools. The result of this paper is we can know and understand at least about mathematical learning process in primary school and how to develop high order thinking skill by referring to the development of 21st century learning skills in primary school classes.